Reliability Impact Of Energy Storage In A Wind Integrated Power System - Farihan, Mohamad (Universiti Sains Malaysia, 2017)
This thesis presents the reliability evaluation of wind farms incorporating with energy storage. Wind power are intermittent in nature, and may cause risk for continuous power supply. In order to minimize the risk, energy storage is introduced where it is used to supply power to the system when wind power is inadequate. Monte Carlo Simulation is used in this research to evaluate generating system reliability. This method described in this thesis are tested using IEEE Reliability Test Systems, in which it has been modified for research purpose. In this approach, a few parameters are tested to evaluate effects of the parameters adjusted towards the working scenario of an energy storage. Reliability studies conducted on wind systems incorporated with energy storage demonstrates that overall power system reliability increases with the aid of energy storage. The energy storage reliability and the power system reliability as a whole can further be improved by selecting the most appropriate working scenarios for the energy storage. This is illustrated by the implementation of two different models of energy storage to the system.